What are heritage values? Integrating natural and cultural heritage into environmental valuation. Issue 2 (30th July 2022) - Azzopardi, Elaine; Kenter, Jasper O.; Young, Juliette; Leakey, Chris; O'Connor, Seb; Martino, Simone; Flannery, Wesley; Sousa, Lisa P.; Mylona, Dimitra; Frangoudes, Katia; Béguier, Irène; Pafi, Maria; et al.
Abstract: There are strong links between heritage and the environment yet, heritage is not fully included in existing ecosystem‐based frameworks. Different understandings of heritage values exist, and heritage values are not yet related to key value categories in environmental values research. To address this gap and facilitate a common values‐based approach, we develop a novel framework that links heritage and environmental values. First, we expand the understanding of heritage values by linking heritage to key environmental value categories. We then use the Life Framework of Values to show how heritage features in the different ways in which people relate to the world. The resulting heritage values framework is operationalised by applying it to six case examples drawn from participatory research on the governance of European coastal and maritime heritage. We found that the environment was not only considered to be a setting for heritage but was itself valued as heritage in different ways; that heritage is not extrinsic to the environment but is also a way in which people see meaning in the environment; and that multiple value frames and types were involved in shaping this perspective. The results highlight important discrepancies between stakeholders' perspectives and existing management approaches. Applying the framework shows the ways in which heritage and nature are entwined by providing a structure for elucidating what can be valued as heritage, what values can inform heritage values and how heritage values feature in human–nature relations. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Résumé: Malgré les liens très étroits qui existent entre l'Environnement et le Patrimoine, ce dernier n'est pas pleinement pris en compte dans les cadres de l'analyse écosystémique. Pour le moment, aucun lien n'est établi entre les différentes conceptions existantes de la valeur patrimoniale et les principales catégories retenues par la recherche portant sur les valeurs environnementales. Pour combler cette lacune et faciliter l'adoption d'une approche commune fondée sur les valeurs, nous avons élaboré un nouveau cadre d'analyse alliant valeurs patrimoniales et valeurs environnementales. Pour cela, nous avons enrichi la compréhension des valeurs patrimoniales en reliant le patrimoine aux principales catégories de valeurs environnementales. Puis nous avons utilisé le cadre d'analyse « Life Framework of Values » afin de montrer comment le patrimoine s'inscrit dans le rapport des individus au monde. Le cadre des valeurs patrimoniales qui en résulte a été opérationnalisé en l'appliquant à six exemples issus d'une recherche participative portant sur la gouvernance du patrimoine côtier et maritime européen. Trois principaux éléments peuvent être soulignés: (i) que l'environnement n'est pas uniquement considéré comme un cadre / écrin pour le patrimoine, mais qu'il est lui‐même valorisé en tant que patrimoine; (ii) que le patrimoine n'est pas extrinsèque à l'environnement, mais qu'il est une composante de la manière dont les individus perçoivent l'environnement et lui donnent sens; (iii) et que de multiples modèles et types de valeurs sont impliqués dans la définition de cette approche. Les résultats mettent en évidence des divergences importantes entre les points de vue des parties prenantes et les approches de gestion existantes. L'application de ce cadre d'analyse montre la manière dont le patrimoine et la nature sont liés. Il fournit une structure permettant de déterminer ce qui peut être valorisé en tant que patrimoine; les valeurs pouvant alimenter les valeurs patrimoniales; et de quelles manières les valeurs patrimoniales s'expriment dans les relations homme‐nature.